2016
DOI: 10.1016/j.ijantimicag.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing auranofin for the treatment of cutaneous staphylococcal infections

Abstract: The scourge of multidrug-resistant bacterial infections necessitates the urgent development of novel antimicrobials to address this public health challenge. Drug repurposing is a proven strategy to discover new antimicrobial agents; given that these agents have undergone extensive toxicological and pharmacological analysis, repurposing is an effective method to reduce the time, cost and risk associated with traditional antibiotic innovation. In this study, the in vitro and in vivo antibacterial activities of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 32 publications
1
62
0
Order By: Relevance
“…The traditional route of antifungal innovation and regulatory approval is a time-consuming, expensive venture. This has led researchers to explore alternative approaches, such as drug repurposing, to expedite anti-infective drug development [27,31,5558]. …”
Section: Discussionmentioning
confidence: 99%
“…The traditional route of antifungal innovation and regulatory approval is a time-consuming, expensive venture. This has led researchers to explore alternative approaches, such as drug repurposing, to expedite anti-infective drug development [27,31,5558]. …”
Section: Discussionmentioning
confidence: 99%
“…Independent of its antirheumatic effect, several studies have reported the anti-infective properties of this drug against important parasitic and bacterial pathogens including Schistosoma mansoni, Trypanosoma brucei, Plasmodium falciparum, Entamoeba histolytica, Staphylococcus aureus , and Streptococcus pneumoniae (Jackson-Rosario et al, 2009; Debnath et al, 2012; Cassetta et al, 2014; Harbut et al, 2015; Thangamani et al, 2016a,b). However, a dichotomy exists regarding the antimicrobial MOA of auranofin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several reports have demonstrated that auranofin, an orally bioavailable FDA-approved drug for treatment of rheumatoid arthritis, exhibits potent antibacterial and antiparasitic activities (Jackson-Rosario et al, 2009; Debnath et al, 2012; Cassetta et al, 2014; Hokai et al, 2014; Aguinagalde et al, 2015; Thangamani et al, 2016a,b). This discovery led to the FDA granting auranofin Orphan Drug status for treatment of amebiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, auranofin was approved by FDA for phase II clinical trials for cancer therapy. The mechanism of action of auranofin involves the inhibition of redox enzymes such as thioredoxin reductase, induction of endoplasmic reticulum (ER) stress and subsequent activation of the unfolded protein response (UPR) (2)(3)(4)(5). Inhibition of these redox enzymes leads to cellular oxidative stress and intrinsic apoptosis (6,7).…”
mentioning
confidence: 99%